Integrating CBT and third wave therapies : distinctive features - Kennedy, Fiona (Fiona Clare); Pearson, David (David G.) (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Integrating CBT and Third Wave Therapies offers a thought-through approach to integrating evidence-based therapies. It provides help for all of us who are developing or have expertise in a variety of evidence-based approaches. The theoretical part of the book briefly reviews four therapies, namely: CBT, DBT, ACT and CFT. The authors identify core processes of change and examine how each therapy contributes to each core process, helping in the integration of all four. The text considers the influence of early adversity on later mental wellbeing, the theoretical underpinnings of mindfulness, behaviour analysis, reliving and re-scripting and dissociation. Theory and practice chapters are illustrated using case vignettes. The book will be useful for therapists to structure sessions with clients. It demonstrates how to follow a theoretical approach and a offers a therapeutic structure for integrated clinical work. It will be useful in reflective practice and supervision, and for students learning about a variety of therapeutic approaches"--
OCLC-licensed vendor bibliographic record.
Keywords: Cognitive therapy; Evidence-based medicine; PSYCHOLOGY / Mental Health